Oxaliplatin in lymphoma (Hematology Meeting Reports, 2009)
To day, 50 to 60% of patients with diffuse large cell lymphoma (DLCL) are cured by conventional chemotherapy but the outcome of patients who either fail to respond or relapse remains very poor. High dose therapy (HDT) followed by autologous stem cell support (ASCS) has become the standard option for such patients in failure. Complete response rates to fist-line treatment with anthracyclin-containing CHOP or CHOP-derived regimens are about 70%, with 5% toxic deaths, 10-15% partial responses and 10% primary failure. Among failures, relapses occurring in patients who first reached complete response are the most frequent event and despite salvage treatment have a 5y-survival of 30%-40%. Late relapses (occurring after one year of remission duration) have a better outcome than early relapses whose prognosis is close to that of primary failures.